METHODOLOGICAL OPTIONS FOR THE USE OF EDUCATIONAL MODELS IN MATHEMATICS LESSONS IN PRIMARY SCHOOL - M.A. Urban (Academy of Cognitive and Natural Sciences, 2010)
This article is devoted to the way of integration of the models to the process of primary math's education. There are some contradictions in this sphere of pedagogics . On the one hand there is a scientifically grounded fact, that the modeling is one of the effective methods of teaching. But on the other hand teachers are not still ready to use it. Six ways of using models in the process of primary school math's education are presented in the article.